The impact of research on policy: a case of qualifications reform - Noyes, Andrew; Adkins, Michael (Wiley-Blackwell, 2016)
The relationship between research and policymaking has been discussed repeatedly. However, the debate tends to be in general, abstract terms or from a macro-economic perspective with any examples described in a fairly cursory way. Despite the inherent complexity of the research-policy interface, analyses tend to homogenize ‘research’ and ‘policy’ as coherent entities with discussions often focusing on products (research and policies) rather than on the relationships between producers (researchers and policy makers). Here we take one piece of research on qualifications that has influenced policy rhetoric over the last 5 years. We trace the career of the research from its production in the late 1990s in order to understand the conditions of its dormancy, reemergence and use over the ensuing years. The paper serves to document the case, which is important in its own right, but also proposes a typology of ways in which research gets adopted and adapted into policy.